Blue Economy Indonesia to Increase National Income through the Indian Ocean Rim Association (IORA) in the Order to Empower the World Maritime Axis and Strengthen State Defense - Duha, Junindra; Saputro, Guntur Eko (Graduate Program Magister Manajemen Pendidikan, 2022)
The joining of Indonesia as one of the states in the Indian Ocean Rim Association (IORA), is an opportunity and correlates with one of the policies of the Government of President Jokowi in an effort to realize Indonesia as the World Maritime Axis based on geo-strategy and geo-economics as an archipelagic country. The research method uses descriptive qualitative. The results of the study show that the blue economy is a very profitable strategy for Indonesia to increase National Income and be sustainable and support national defense through the Indian Ocean Rim Association (IORA). This research provides benefits on how to improve the management of the vision of the World Maritime Axis through Indonesia's Blue Economy To increase National Income through the Indian Ocean Rim Association (IORA) in the context of Realizing the World Maritime Axis and Strengthening National Defense the study of Defense Science. The novelty of this research is that it combines the concept of a blue economy with the study of defense science studies to anticipate threats from within and outside the country